Stress assessment of argan (Argania spinosa (L.) Skeels) in response to land uses across an aridity gradient: Translational asymmetry and branch fractal dimension - ALADOS, C L; El Aich, A (Journal of Arid Environments, 2008)
We used Translational Asymmetry (TA) of the annual stem, branch growth pattern and fractal dimension to quantify stress during development of argan (Argania spinosa (L.) Skeels) throughout its range in Morocco. Under communal grazing conditions known as ‘‘mouchaˆa’’ (Grazing Management), the branch fractal dimension was reduced and the TA of plants increased, reﬂecting the stressful conditions in which the argan trees were growing. Under Wild growing conditions, developmental instability increased as moisture decreased across a gradient of aridity. Under Barley Management conditions (barley crops are cultivated underneath of argan), argan increased branch complexity (branch fractal dimension) in the mildest area (Essaouira), which imposed an additional cost that results in increased TA. The results of the study best ﬁt the predictions that the level of asymmetry and fractal dimension reﬂects stressful conditions, which can be used to monitor the effect of environmental stress in the conservation of argan ecosystem.
Keywords: argan; aridity; developmental instability; environmental stress; fractal; Grazing; land use; translational asymmetry